Long-run projections of environmental impact in the OECD: the importance of uncertainty and age structure. (1st January 2011) - Liddle, Brantley
This paper considers the influence of uncertainty with respect to GDP and population – total and age structure – on long-run environmental impact projections. A simple model, based on the stochastic version of the IPAT equation, is used to generate projections of two environmental impacts for which population has a demonstrated influence – carbon emissions from transport and residential electricity consumption. The paper examines the sensitivity of those long-run projections to uncertainty regarding possible future GDP and population growth/change. The following are demonstrated: 1 if the medium path for either population or GDP is to be believed/trusted, then uncertainty with respect to the growth/change of the other factor is unimportant 2 uncertainty with respect to population projections has a greater effect on environmental impact projections than does uncertainty with respect to GDP projections – despite that the degree of uncertainty associated with population is smaller than the uncertainty associated with aggregate economic growth.